Environmental biomonitoring plants for sustainable nature protection - Paradiž, Jasna (Journal for Geography, 2011)
In the past 10 years of biomonitoring on the Ljubljana moor, population status and distribution changes of Fritillaria meleagris and Solidago canadensis were investigated. Plant bioassays were also performed for the environmental hazard assessment in wetlands. Spatial distribution maps showed decreased population densities of F. meleagris at observed sites but increased distribution size of S. canadensis through the area. Cytogenetic analyses of different species indicated an elevated genotoxic hazard for plants inhabiting the nearby surrounding moor of Ljubljana in comparison to other localities. Monitoring plants for early signalling of harmful pollution effects and ecosystem ecoremediations as the most sustainable protection measure for plants in natural environments could be suggested.